2007
DOI: 10.1590/s0101-31222007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do ambiente de armazenamento na qualidade de sementes de sorgo-sudão

Abstract: RESUMO -O trabalho objetivou avaliar efeitos do ambiente de armazenamento na qualidade de sementes de sorgo-sudão (Sorghum sudanense (Piper) Stapf) de diferentes procedências. Cinco lotes de diferentes origens foram armazenados por nove meses, acondicionados em sacos de papel unifoliado, em quatro condições ambientais: ambiente natural de laboratório (sem controle de umidade relativa e temperatura); 30 a 40% de umidade relativa e sem controle de temperatura (simulada através de câmara seca); 10 a 15% de umidad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
2
0
1
Order By: Relevance
“…These results corroborate those obtained for sudangrass (Sorghum sudanense) seeds, in which the refrigerator and freezer environments, followed by the dry chamber, led to more adequate conservation than the natural laboratory environment, which had faster loss of vigor (Toledo et al, 2007;Toledo et al, 2013). In black oat seeds, the refrigerator and freezer environments were also more favorable for conservation than the dry chamber environment and natural environment (Nakagawa et al, 2004).…”
Section: Dry Chambersupporting
confidence: 85%
See 1 more Smart Citation
“…These results corroborate those obtained for sudangrass (Sorghum sudanense) seeds, in which the refrigerator and freezer environments, followed by the dry chamber, led to more adequate conservation than the natural laboratory environment, which had faster loss of vigor (Toledo et al, 2007;Toledo et al, 2013). In black oat seeds, the refrigerator and freezer environments were also more favorable for conservation than the dry chamber environment and natural environment (Nakagawa et al, 2004).…”
Section: Dry Chambersupporting
confidence: 85%
“…The data on moisture content of the seeds stored in the four different environments for the period of six years in the natural laboratory environment and dry chamber and for twelve years in the refrigerator and freezer are shown in Table 1. The moisture contents varied in the different environments due to the seeds being stored in porous packaging, which facilitates hygroscopic equilibrium in accordance with relative humidity (Toledo et al, 2007;Toledo et al, 2013;Costa et al, 2015). The seeds stored in the different environments had mean moisture contents of 9.9, 9.7, 5.9 and 13.2% for the natural laboratory environment, dry chamber, refrigerator, and freezer, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Um dos fatores que mais influenciam a germinação e vigor das sementes é o armazenamento, Toledo (2007) afirma que a capacidade de conservação de sementes de S. sudanense está relacionada com a sua qualidade inicial dependente da sua origem, além disso, outros danos tais como ataque de patógenos e problemas com temperatura podendo comprometer um lote de sementes bem como a produtividade forrageira.…”
Section: Methodsunclassified
“…Under natural environment conditions, moisture content may vary depending on oscillations in relative humidity and, along with temperature variations, can determine deterioration rates in seeds and physiological quality losses. According to Toledo et al (2007), in the first stage of this study, storage of sudangrass seeds in frost free e freezer environments improves physiological quality. Similarly, Nakagawa et al (2004) found that maintaining seeds in frost free and freezer conditions can preserve physiological quality of black oat seeds compared to storage in dry chamber.…”
Section: The Equation Adjusted To Mean Germinationmentioning
confidence: 99%